Diseño de un arranque y control de velocidad de un motor de inducción jaula de ardilla (mija), que permita optimizar el consumo de energía dentro de un proceso industrial - Pilaquinga Cantuña, Francisco Xavier (2015)
This research project is focused on the analysis of energy saving making the comparison with different types of startup: Direct Boot, Boot Star - triangle, Start with frequency with which you want to compare energy consumption in these types start and arrive at recommendations based on the results. The tools used in the project for the engine control and monitoring electronics are commonly found on the market but the most prominent are the HMI KTP 400, the variable speed drive Sinamics G110, SIEMEN PLC S7-1200 and software TIA PORTAL V13 which to be interconnected are helpful to reach the desired conclusions. The analysis of the project carried out under vacuum conditions (load), for working conditions has been implemented to the engine made a braking mechanism shaft and measurements were carried out simulating the load 2 starts measuring they are done in a time range of 5 minutes that consumption is projected for consumption of one hour, it is projected for consumption of a working day of 12 hours / day, and annual consumption is projected to different processes boot. It is to conclude that the investment in the purchase of an inverter and the implementation of an automatic system with PLC and HMI during the time it is a good investment.